Future airport terminals: new technologies promise capacity gains - Kalakou, S.; Psaraki-Kalouptsidi, V.; Moura, F. (Journal of Air Transport Management, 2015)
The changing dynamics of passenger processes in future airport terminals resulting from pressures from both the demand and supply side are analyzed in this paper. Short and long term (beyond 2020) developments are studied following technology advances and business plans of airlines and airports. Key technologies affecting the central passenger processing functions include identity management and biometrics, Near Field Communications, Big Data analytics and smartphone applications. A simulation model is developed and used to assess the impact of forthcoming changes on the airport's departure hall. Lisbon Portela airport is used as case study. It is shown that passenger process times at the check-in and security checkpoints are significantly reduced, due to the introduction of passenger facilitation processes, under a range of behavioral, technological and policy uncertainties. The most salient implication of these reductions is the quantified capacity gains in the building which question the need for terminal expansion.